An Exploration of the Intellectual Capital of the Biotechnology Industry: The Experience of Taiwan - Lin, Hsiukan; Chang, Tsangyao; Yeh, Chuntsen (Journal of Asian Business Strategy, 2013)
The biotechnology industry is one of the six emerging industries in Taiwan. Taking listed on the Taiwan Stock Exchange (TSE) companies and over-the-counter (OTC) companies which form part of the biotechnology healthcare industry in Taiwan during the period 1996-2008 as the research object, this paper uses factor analysis and regression models to explore the critical intellectual capital (IC) factors influencing enterprise value, with the aim of providing relevant information regarding the biotechnology industry to the administering authority to use as a reference. According to the empirical research results: (1) human capital, process capital, internal innovation capital, external innovation capital and customer capital are five critical IC factors (dimensions) influencing the value of the biotechnology industry; (2) human capital, internal innovation capital and external innovation capital have a significant and positive relationship with the creation of enterprise value, while process capital and customer capital have a negative impact on the creation of enterprise value; and (3) Taiwan’s biotechnology companies should improve their process capital and customer capital in order to create enterprise value effectively.